2013
DOI: 10.1136/archdischild-2012-303113
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiology of coeliac disease in South Wales: a 28-year perspective

Abstract: The frequency of diagnosis of CD in this defined population has continued to rise, with an increase in the median age at diagnosis, and over 50% of patients exhibited few or no symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 7 publications
1
19
0
2
Order By: Relevance
“…En la última década ha quedado claro que el número de pacientes celíacos conocidos es muy inferior al que está diagnosticado [11][12][13] . En buena parte esto se debe a que, anteriormente, la enfermedad se buscaba solamente en personas que se sentían enfermas y consultaban al médico.…”
Section: ¿En Quienes Debemos Buscar Enfermedad Celíaca?unclassified
“…En la última década ha quedado claro que el número de pacientes celíacos conocidos es muy inferior al que está diagnosticado [11][12][13] . En buena parte esto se debe a que, anteriormente, la enfermedad se buscaba solamente en personas que se sentían enfermas y consultaban al médico.…”
Section: ¿En Quienes Debemos Buscar Enfermedad Celíaca?unclassified
“…During the epidemic period, the incidence rate of CD children detected clinically under the age of 2 years increased four-fold in comparison to the time period before (pre-epidemic period) and after (post-epidemic period) (Namatovu 2014). A plethora of studies indicates that the incidence rate of pediatric CD increased during the latest years, varying though worldwide a, Whyte 2013, Zingone 2015.…”
Section: Incidence and The Swedish Epidemic Of CDmentioning
confidence: 99%
“…Studies from various countries (Ludvigsson 2012, Whyte LA. 2013, White 2013, Namatovu 2014, Zingone F. 2015 confirm the increase of CD incidence rate during the recent years.…”
Section: Incidence Ratementioning
confidence: 99%
“…There are substantially fewer paediatric gastroenterologists than adult specialists, in the UK and across Europe. There has also been an increase in demand for paediatric endoscopy, not only due to the increase in recognition of children with coeliac disease, 5 but also to increasing numbers of children requiring endoscopy for inflammatory bowel disease and emerging disorders such as eosinophilic oesophagitis. Therefore publication of studies that demonstrated that a high titre of IgA tTG antibodies accurately predicted the finding of diagnostic histological changes on biopsy were important.…”
Section: Coeliac Disease: a Common Disordermentioning
confidence: 99%
“…There has therefore been a shift towards recognition of people with more subtle symptoms, but even now around 80% of cases remain unrecognised in both adults and children compared with what would be expected in a screening programme. 5 The long-term consequences of truly asymptomatic coeliac disease are unknown, and, as such, population screening is not yet indicated. However, the challenge is to identify people with active coeliac disease but relatively subtle symptoms.…”
Section: Coeliac Disease: a Common Disordermentioning
confidence: 99%